EFEKTIVITAS ABSENSI FINGER PRINT TERHADAP KEDISIPLINAN PNS DI KANTOR SEKRETARIAT DAERAH KOTA SUBULUSSALAM - Restika Deriyani; Vellayati Hajad (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2022)
This study is about the effectiveness of finger print attendance on the discipline of civil servants at the Regional Secretariat Office of Subulussalam City. Discipline is how a person’s attitude is in obeying and obeying what has been set as responsibility. Different opinions say, if discipline is a necessity as well as a demand in people’s lives. This study aims to look at employee discipline in implementing finger print absenteeism. This study used qualitative research methods and data were collected through interviews and observations. The results of this study indicate that the implementation of the finger print absence has slightly increased the discipline of civil servants, and in the implementation of the finger print absence there are still several obstacles such as machine effors, sometimes unsupportive networks and machine maintenance that must be done regularly. The conclusion of this study is that finger print attendance has gone well and affect employee discipline, however, there are inhibiting aspects such as network problems and employee attitudes.